On How Thermal Annealing Affects the State Of Clusters Of Nickel Atoms In Crystal Lattice Of Silicon - M.K. Bahadirkhanov, B.K. Ismaylov, K.A. Ismailov, N.F. Zikrillaev, S.B. Isamov (International Journal of Advanced Science and Technology, 2020)
The authors report the phenomenon of migration of clusters of impurity atoms of nickel in crystal lattice of silicon. It is shown that the clusters migrate through the silicon crystal lattice while having anomalously high diffusion coefficient (D 10-9 cm2/s at T = 800°C). The authors have been able to determine the composition of such clusters and propose a model of its structure, as well as the mechanism of diffusion.